Efficacy and safety of platelet-rich plasma combined with core decompression and enhanced bone grafting versus core decompression with enhanced bone grafting alone in treating femoral head necrosis: a systematic review and meta-analysis - Yunqi Cao; Xiaolei Deng; Siyi Hou; Jian Wang; Bo Wei; Liyou Hu; Decai Hou (Journal of Orthopaedic Surgery and Research)
Abstract Background The efficacy and safety of platelet-rich plasma (PRP) combined with core decompression (CD)-enhanced bone grafting for the treatment of osteonecrosis of the femoral head remains controversial. This study aimed to conduct a systematic review and meta-analysis of the efficacy and safety of PRP combined with CD-enhanced bone grafting for treating osteonecrosis of the femoral head and to compare this method with CD-combined bone grafting as a way to provide theoretical bases for future clinical treatments and research. Objective This study aimed to assess the improved efficacy and safety of core decompression combined with platelet-rich plasma-enhanced bone grafting for osteonecrosis of the femoral head compared to core decompression-enhanced bone grafting. Method We systematically searched several databases for randomised controlled trials comparing bone graft and core decompression with or without PRP, including 16 studies involving 999 subjects and 1139 hip cases. This meta-analysis followed the Preferred Reporting Items (PRISMA) guidelines. The study is registered with PROSPERO under code CRD42024557968. Result 16 articles involving 999 patients (1139 hips) were included in this study. Pooled analyses demonstrated that when core decompression-enhanced bone grafting was combined with PRP, the Harris hip score (mean difference [MD]: 5.26, 95% Cl:4.81–5.71; P < 0.00001), visual analog scale (MD: -0.74, 95% Cl:-0.99 – -0.49; P < 0.00001) and reduction in the need for THA: (risk ratio [RR]: 0.29; 95% Cl:0.16–0.53; P < 0.0001) were superior to core decompression-enhanced bone grafting alone. Furthermore, a pooled analysis confirmed the safety of PRP [RR:0.33; 95% Cl:0.13–0.83; P = 0.02]. All these results were statistically significant. Conclusion Compared to CD-enhanced bone grafting, the combination of PRP appears to yield superior therapeutic outcomes in restoring hip function, alleviating pain, preventing THA, and ensuring postoperative safety. Moreover, we require a higher level of randomised controlled trials to evaluate its efficacy and safety.